Realizing Adaptive Learning with Living Intelligence: The Role of AI, Biotechnology, and Smart Sensors in Education - Mariyani, Nia; Anum, Do Intan Putri; Restiawati, Rista Adhani; Fitrawan, Harun; Hardian, Dafyar Eliadi (MSJ : Majority Science Journal, 2025)
The 21st century demands an education system that is adaptive, personalized, and responsive to the diversity of learners. The integration of Artificial Intelligence (AI), biotechnology, and smart sensors within the concept of living intelligence offers a transformative solution for realizing dynamic, evidence-based learning. AI utilizes real-time analytics, knowledge tracing, and multimodal modeling to map students' cognitive, affective, and contextual states, allowing for prescriptive and anticipatory learning interventions. Biotechnology and smart sensors enrich the system with biometric indicators such as heart rate variability (HRV), electrodermal activity (EDA), brain waves (EEG), and sleep quality, which are analyzed synchronously to monitor learning readiness in real time. This approach combines cognitive, affective, and physiological dimensions within a single, interconnected ecosystem. Challenges such as algorithmic bias, data privacy, concept drift, and infrastructure limitations are addressed through privacy-by-design governance, federated learning, and explainable AI. The role of the teacher shifts to that of a curator of meaning and a data-driven decision-maker, while the open learner model provides space for student participation. Through multidisciplinary collaboration and ethical policies, living intelligence becomes a new paradigm for education that is inclusive, sustainable, and capable of forming lifelong learners who are relevant to future demands